Quando elas vestem o colarinho branco : análise das intersecções de gênero, raça e classe no julgamento de mulheres criminalizadas no âmbito da lava-jato - Oliveira, Manoela Mousquer de (2021)
The significant increase in the incarceration rates of women since the 2000s caused an increase in researches aimed at female criminality. However, there are few studies researching the gender perspective applied to the white-collar universe. Therefore, this research aimed to understand, under the theoretical-methodological paradigm of Feminist Criminology, how the female role in crimes related to Lava-Jato is presented by the criminal justice system in decisions in the first degree of jurisdiction. To this end, four court rulings were qualitatively analyzed to determine the accountability or not of women for the alleged crimes of money laundering, passive corruption, and criminal association. Through the gender, race, and class sphere, we sought to contrast some differences in the judgment of the accused and many others involved in street criminality. As a methodology, we used a literature review combined with case study in multiple modalities since both techniques, taken in isolation, would be insufficient to achieve relevant results. As a result, it was concluded that the underrepresentation of women in white collar related crimes is directly linked to the fact that women are still few in political, management and power positions. Added to this, non-white women are even more discriminated against due to disparity, as they are subjected to the regime of racial domination, they are socially, economically, and politically more vulnerable. Finally, it was found that gender stereotypes still play a determining role in the construction of the condemnatory or acquittal decisions, considering that the non-compliance with the rules of behavior to be followed by men and women implies a double disapproval.